Optimal Economic Policy and the Problem of Instrument Instability - Holbrook, Robert S. (American Economic Review, 2016)
It has been said that in a world of perfect knowledge regarding the structure of the economic system and the values of all exogenous variables, policy making becomes a trivial problem.1 This is true in the sense that it is always possible, with full knowledge and perfect foresight, to choose the appropriate policy for the following period, but it ignores the fact that the correct policy on a period to period basis may turn out to be impractical or even impossible in the longer run. Current policy decisions do not ordinarily have their impact solely in the current period, but rather over a number of periods in the future. Thus, in addition to offsetting the undesired effects of changes in exogenous variables, current policy decisions must offset the current impact of past policy